The Association Between Organizational Characteristics and Strategic Information Systems Planning: A Study of U.S. Hospitals - Upadhyay, Soumya; Opoku-Agyeman, William; McCaughey, Deirdre; Burke, Darrell E. (European Scientific Journal, ESJ, 2017)
Despite the potential of Strategic Information System Planning (SISP) to reduce cost and improve quality, hospitals have been slow to have strategic plans on Information Systems. Our objective was to explore which organizational characteristics influence SISP in healthcare. Data on Information Systems plans from the HIMSS analytics database was combined with organizational characteristics data from the American Hospital Association. Logistic regression analyses on a sample of 2,495 hospitals revealed that hospitals with system membership and for profit status had a greater likelihood of selecting ‘computerized medical records’ (OR=1.88, OR=6.60 respectively, p<0.05), ‘decreasing medical errors’ (OR=7.02, p<0.05), ‘resolving integration issues’ (OR=1.36, OR=0.15 respectively, p<0.05), ‘migrating towards a paperless environment (OR=1.66, OR=8.28 respectively, p<0.05), and ‘reducing the number of software vendors’ (OR=1.78, OR=0.23 respectively, p<0.05) as their Information System plans. System membership and ownership status are associated with SISP. An understanding of the hospital characteristics that may impact Strategic Information Systems Planning, managers would assist managers in making informed decisions about planning and implementing Information Systems at their hospitals.